2001
DOI: 10.1159/000046702
|View full text |Cite
|
Sign up to set email alerts
|

In situ Metabolic and Hemodynamic Response to Dexfenfluramine in White Adipose Tissue of Rats

Abstract: Serotonergic neurons are included in the regulation of eating behavior and energy metabolism. Dexfenfluramine (DF), a serotonin releaser and reuptake inhibitor, is known to reduce food intake and body weight and to improve the metabolic profile of obese subjects with and without metabolic complications such as type 2 diabetes. Due to cases of valvular heart diseases, DF was withdrawn from the market in 1997. However, serotonergic drugs are still used in clinical practice. We studied the hemodynamic and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This may imply that decreased salt intake and food intake can be caused by sertraline and imipramine which are both serotonergic agents. Imipramine has previously been reported to decrease preference for sweets in depressed patients (Fernstrom et al, 1987) and sertraline has been shown to be able to reduce salt appetite (Lima et al, 2004) and serotonergic agents are known to be able to reduce food intake and weight (Boschmann et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This may imply that decreased salt intake and food intake can be caused by sertraline and imipramine which are both serotonergic agents. Imipramine has previously been reported to decrease preference for sweets in depressed patients (Fernstrom et al, 1987) and sertraline has been shown to be able to reduce salt appetite (Lima et al, 2004) and serotonergic agents are known to be able to reduce food intake and weight (Boschmann et al, 2001).…”
Section: Discussionmentioning
confidence: 99%